Profiling learners and teachers at remote rural secondary schools: a case study - Delport, A.; Mangwaya, Ezron (Taylor & Francis, 2016)
The academic achievements of learners at remote rural secondary schools in developing countries like Zimbabwe and South Africa tend to be low compared to those who attend urban schools. Acknowledging that numerous factors are likely to influence learners’ academic achievement in general, this study focused on two factors, which have been identified by research as particularly significant, namely the specific profile of the rural school learner, as well as the profile of the teacher teaching at these rural schools. Although our actual investigation was in the form of a case study done at only two remote rural secondary schools in Zimbabwe, we believe that these schools resemble most remote rural secondary schools in developing countries, also in South Africa. Based on our findings, we contend that the poor academic performance of learners at these two remote rural schools can be related to the specific profiles of the learners who attend these schools, as well as the profiles of teachers teaching at these schools. Although our investigation did not reveal significant new insights, it once again emphasised the continuation of the dilemma of bimodal distribution of education opportunities to the detriment of (mainly black) learners in remote rural areas. Until such time that this problem is successfully addressed, it needs to remain on the education agenda.